OPEN ACCESS: Insights into UK farmers' attitudes towards cattle youngstock rearing and disease. (2nd November 2020) - Baxter-Smith, Katharine; Simpson, Robert
Abstract : There is increased industry focus on optimised welfare, productivity and antibiotic usage in cattle youngstock, however, little is known about UK farmers' attitudes and practices in rearing calves. In this cross-sectional study, 479 farmers were surveyed online about their cattle youngstock rearing approach and outcomes. Represented were 174 dairy farmers, 255 beef suckler farmers and 50 calf rearers. Farmers showed awareness of good youngstock rearing practices such as colostrum management and housing facilities. Morbidity and mortality from diarrhoea (82%, 48%) and bovine respiratory disease (BRD) (68%, 48%) were high on farms surveyed but farmers did not frequently consult their veterinary surgeon regarding these diseases. Farmers surveyed were not always aware of the efficacy of preventative methods such as vaccination, and frequently used antibiotic treatments (27% for diarrhoea and 40% for BRD) but not diagnostics when animals had disease. Veterinary surgeons could use these insights to better understand farmers' motivations and priorities, to make communication more efficient and align goals.